Eco-Innovation as a Positive and Happy Industry Externality: Evidence from Mexico - Galván Vela, Esthela; Ruíz-Corrales, Missael; Ahumada-Tello, Eduardo; Ravina-Ripoll, Rafael (My University, 2023)
Abstract: This research has carried out structural equation modelling to empirically examine whether Mexican industrial firms have a green policy to reduce their environmental impact. It will allow them to enjoy sustainable development based on eco-innovation and happiness management principles. This type of innovation can be initiated by the companies’ own will or by external factors, such as market requirements, the demands of customers, consumers, suppliers, and civil society through corporate social responsibility. The findings of this article highlight three main aspects. The first is that the statistically analysed eco-innovation actions undertaken by the companies are essentially motivated by market pressures through customers, the financial sector, and civil society. Secondly, economic incentives in Mexico are crucial for manufacturing companies to implement environmentally friendly production patterns within their organisations since this generates the possibility of developing new businesses. Furthermore, eco-innovation generates competitive advantages when the production of the examined companies minimises environmental pollution. It allows access to new markets. In this way, eco-innovation becomes a cornerstone in the economic and international growth of the corporations in this study. RESUMEN Esta investigación ha llevado a cabo modelos de ecuaciones estructurales para examinar empíricamente si las empresas industriales mexicanas cuentan con una política verde para reducir su impacto ambiental les permitirá disfrutar de un desarrollo sostenible basado en principios de ecoinnovación y gestión de la felicidad. Este tipo de innovación puede iniciarse por voluntad propia de las empresas o por factores externos, como requisitos del mercado, las demandas de los clientes, consumidores, proveedores y la sociedad civil a través de responsabilidad social empresarial. Los hallazgos de este artículo destacan tres aspectos principales. El primero es que las acciones de ecoinnovación analizadas estadísticamente que llevan a cabo las empresas son esencialmente motivado por las presiones del mercado a través de los clientes, el sector financiero y la sociedad civil. En segundo lugar, los incentivos económicos en México son cruciales para que las empresas manufactureras implementen patrones de producción amigables con el medio ambiente dentro de sus organizaciones, ya que esto genera la posibilidad de desarrollando nuevos negocios. Además, la ecoinnovación genera ventajas competitivas cuando la producción de las empresas examinadas minimiza la contaminación ambiental. Permite el acceso a nuevos mercados. De esta forma, la ecoinnovación se convierte en un pilar fundamental en el desarrollo económico e internacional crecimiento de las corporaciones en este estudio.
Sustainability
Revista indexada en JCR como Q1 y en Scopus
Keywords: eco-innovation; environmental impact; sustainable development; externalities; Campus Tijuana